Integration of Character Education in Subjects at MTsN 1 Pidie Jaya - Fikri; Abdullah, Nazaruddin; Ismail, Nazaruddin (PT. Anagata Sembagi Education, 2025)
This research aims to analyze the integration of character education into subject lessons at MTsN 1 Pidie Jaya. The study uses a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results show that teachers integrate character values according to the characteristics of their respective subjects. Science teachers instill honesty and teamwork through collaborative projects, Islamic Education (PAI) teachers emphasize tolerance and religious moderation, and Civics (PPKn) teachers promote empathy and adherence to legal norms. Meanwhile, counseling (BK) and physical education teachers foster empathy, discipline, and sportsmanship through practical approaches. This integration process has a positive impact on students' character development. Supporting factors include school policies, teacher commitment, and active participation from parents and the community. However, challenges include limited time allocation, inadequate facilities, and a heavy workload for teachers